Conceptual framework for general traceability solution: description and bases. (11th October 2019) - Bougdira, Abdesselam; Ahaitouf, Abdelaziz; Akharraz, Ismail
Abstract : Purpose: The purpose of this paper is to describe a proposed framework for traceability purpose. Hence, the framework provides a formal and structured way of viewing a traceability solution. This structure lays the required bases for a traceability system before starting development and deployment. Design/methodology/approach: The paper examines several traceability publications, including systems and literature review. The study covers the traceability implementation phase. Therefore, this research approaches the traceability issue from three perspectives (description, engineering and executive one). The separation between aspects is essential when describing and comparing traceability systems. This distinction is also helpful when recommending solution improvements. Findings: The framework identifies six traceability bases: aims, functions, specifications, data classification, processes and procedures. These can establish a basis for a general purpose tool that can enable users to develop an efficient traceability solution. Thus, the first ontology expresses the framework domain and ensures optimal use of it. The second one represents the bases that can serve as a knowledge base to manage the product data. Research limitations/implications: The suggested framework tackles the implementation of traceability. Therefore, the design emphasizes the importance of technological concerns. Some studied cases could require more research angles (i.e. economic and legislative). Thus, framework enrichment is essential for further improvements. Practical implications: The framework helps users to develop a general, interoperable and scalable traceability solution. These are important to promote the generalization of traceability systems. Originality/value: The framework fulfills a requirement for establishing general traceability foundations. Therefore, the guide independently operates of the product or the industry specificity. Moreover, the bases aim to bridge the gap between solution engineering and traceability requirements.